Gas and Chemical Lasers and Intense Beam Applications III 2002
DOI: 10.1117/12.465765
|View full text |Cite
|
Sign up to set email alerts
|

Historical perspective of COIL

Abstract: The oxygen-iodine laser was the first electronic transition chemical laser. It first lased 25 years ago at the Air Force Weapons Laboratory (now the Air Force Research Laboratory). The development started several years earlier and involved the support of many people in the laser community. I would like to describe the early thoughts, insights and even misconceptions that we had in the early days. I will also highlight the contributions of many of the people and organizations that contributed to the early devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…They detected 1 2 (X; 25•v"•43) using laser induced fluorescence to probe the products of this quenching process. Following up on this excellent work, we used laser induced fluorescence to probe the dissociation region in a flow of singlet oxygen and molecular iodine and observed a similar distribution of vibrationally hot ground state 12.21 This combined with the prior chemiluminescence results of Heidner, 13 1 4 Lilenfeld, 2223 and Alsing, 17 confirmed that iodine was an active participant in its own dissociation.…”
Section: Resonance Absorptionmentioning
confidence: 79%
See 2 more Smart Citations
“…They detected 1 2 (X; 25•v"•43) using laser induced fluorescence to probe the products of this quenching process. Following up on this excellent work, we used laser induced fluorescence to probe the dissociation region in a flow of singlet oxygen and molecular iodine and observed a similar distribution of vibrationally hot ground state 12.21 This combined with the prior chemiluminescence results of Heidner, 13 1 4 Lilenfeld, 2223 and Alsing, 17 confirmed that iodine was an active participant in its own dissociation.…”
Section: Resonance Absorptionmentioning
confidence: 79%
“…3 , 4 Using a microwave source for excited oxygen and a temperature controlled flow reactor, they produced kinetic data that are used to this day. From these data they developed possible mechanisms for the molecular iodine dissociation that were discussed earlier by Mike Heaven.…”
Section: Chemiluminescencementioning
confidence: 99%
See 1 more Smart Citation
“…The history and development of COIL has been well documented by McDermott [6], Heaven [7], and others [8]. The first continuous wave AGIL device, demonstrated by Henshaw in 2000 [3], was enabled and inspired by the work of many, including Benard [9], Bower [10,11], Clyne [12][13][14], Coombe and Gilbert [15][16][17][18][19], Heaven [7,20,21], Henshaw [22,23] …”
mentioning
confidence: 99%